Restoration of active pick-up function in patients with total brachial plexus avulsion injuries. (March 2018) - Li, Feng; Wang, Shu-feng; Li, Peng-cheng; Xue, Yun-hao; Zou, Ji-yao; Li, Wen-jun
We designed multiple nerve transfers in one surgery to restore active pick-up function in patients with total brachial plexus avulsion injuries. Forty patients with total brachial plexus avulsion injuries first underwent multiple nerve transfers. These included transfer of the accessory nerve onto the suprascapular nerve to recover shoulder abduction, contralateral C7 nerve onto the lower trunk via the modified prespinal route with direct coaptation to restore lower trunk function and onto the musculocutaneous nerve with interpositional bridging by medial antebrachial cutaneous nerve arising from lower trunk to restore elbow flexion, and the phrenic nerve onto the posterior division of lower trunk to recover elbow and finger extension. At least three years after surgery, the patients who had a meaningful recovery were selected to perform secondary reconstruction to restore active pick-up function. Active pick-up function was successfully restored in ten patients after they underwent multiple nerve transfers combined with additional secondary functional hand reconstructions. Level of evidence: IV